THE LOST-CITY DAN LOST-SPACE KARENA PERKEMBANGAN PENGEMBANGAN TATA-RUANG KOTA Kasus Koridor Komersial Jalan Tunjungan Kotamadya Surabaya - Benny Poerbantanoe (DIMENSI (Journal of Architecture and Built Environment), 1999)
Every town hss its own architectural performance. And architecture is not merely a physical landscape of buildings in a town,, as seen by the observer, but it has a deeper mening, which displays the art of structures and constructions. It is a sequence of buildings along the course of its history (Aldo Rossi, 1980). A Town is a complete work of art, performed by men of urban knowledge. Tehe concept of a town or urban workmanship arises from time to time as a work of art in multiple variations, together and according to spirit of the time, included its aspects of belief and religion. The urban work of art or urban artefact is always related to location, historical events and the spesific urban look. Generally a town has particular rythm and dynamics, at least it does not remain static. Therefore it is quite right, when we say, that a town represents the course of its history and technology during the period of its existence. But when we scrutinise alongthe historical and visual systems, it turns out that so many physical and sociqal spaces have been altered with regard to their quality and quantity, as result mis management ot the physical and social spaces by less careful urban reformists. they may bring about certain inbalancy in the system, destroying public imagination and memory about the identity and message conceived at the time of their construction. At the this may affect a condition, commonly called the lost space. Surabaya is one of the larger towns in Indonesia, which afrtime possessed a number of urban artefacts and workmanship. One of which is the Tunjungan Street, designed and developed by the Gemeente Administration of the Duutch as comercial corriodor of the town, with all its advantages and shortcomings. In spite of the fact that it has never been touched by the hands of the prominent urban planner Mr. Thomas C. Karsten, who has prepared and worked out the architecture of the bigger towns of the former Netherlands Indies like Medan, Jakarta, Bandung, Semarang, Malang and Ujung Pandang with their respective spesific colonial character impression. For the aging generation of the town, Surabaya is called with much regret as the lost city, because of the declining quality of some of its urban artefacts, which once has been their pride and their joy. The abovementioned commercial corridor of Jalan Tunjungan is an example of a lost space Abstract in Bahasa Indonesia : Kota adalah arsitektur. Arsitektur yang bukan sekedar gambar (wujud fisik-visual) dari kota yang bisa dilihat saja, melainkan juga sebagai suatu konstruksi. Yaitu konstruksi dari kota sepanjang waktu (Aldo Rossi, 1980). Kota merupakan karya seni yang sempurna, yang dibuat hanya oleh orang-orang yang benar-benar mengerti tentang urban. Konsep kota atau tepatnya urban-artefak sebagai karya seni selalu muncul dan diketemukan dalam bentuk-bentuk yang bervariasi ; dalam segala jaman dan kehidupan sosial-religius. Urban-artefak selalu berkaitan dengan tempat, peristiwa dan wujud-kota. Kota pada umumnya mempunyai sifat dinamis, alias tidak statis. Oleh karena itu tidaklah berlebihan apabila terdapat pernyataan umum yang menyebutkan bahwa; kota itu adalah lambang perjalanan sejarah, teknologi dan jamannya. Namun jika disimak dari sistem-sejarah maupun sistem-visual. Banyaknya ruang fisik dan sosial telah berubah baik secara kwalitas maupun kwantitas, sebagai konsekwensi logis adanya pertumbuhan (perkembangan dan pengembangan) dari ruang fisik dan sosial, yang belum dikelola secara benar dan baik. Bisa mengganggu keseimbangan , serta merusak kesan dan memori publik tentang identitas dan citra. Yang akhirnya akan dapat melahirkan apa yang disebut dengan lost space. Surabaya adalah salah satu kota besar di Indonesia, yang memiliki beberapa artefak-urban yang spesifik. Salah satunya yaitu jalan Tunjungan; yang pernah didesain serta dikembangkan pada masa pemerintahan Gemeente, sebagai "koridor komersial" Belanda dengan segala kelebihan dan kekurangannya. Walaupun tidak sampai tersentuh oleh tangan Thomas C. Karsten, seorang planolog Belanda yang berkarakteristik untuk desain kota-kota kolonial di Indonesia sebagaimana kota-kota besar lainnya, seperti; Medan, Jakarta, Bandung, Semarang, Malang, Ujung-pandang. Bagi generasi tua, Surabaya kini kemudian terkenal dengan dengan julukan the lost city, karena menurunnya beberapa kwalitas artefak-urban yang dimilikinya. Dimana salah satunya adalah koridor komersial jalan Tunjungan tersebut diatas. Kata kunci: Koridor jalan Tunjungan, Kotamadya Surabaya, Kota yang hilang (Lost-City), Ruang luar yang mubasir (Lost-space)